Analysis of Single N-P-Ca and Compound NPCa Fertilizer Input Levels on the Growth andBiomass Production of Elephantgrass (Pennisetum purpureum cv. Merkeron) - Muhtar, Muhamad (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2024)
The successful growth of elephantgrass (Pennisetum purpureum cv. Merkeron) is reflected in the high and low levels of forage production and quality. Successful growth of forage requires physical environmental support from ideal soil and climate as well as the treatment process provided. This research was conducted using a completely randomized design with 7 treatments and 3 replications. Fertilizer use are single N-P-Ca fertilizer and compound NPCa fertilizer. The dosage of single N-P-Ca fertilizer and compound NPCa fertilizer is adjusted to the rules stated on the label issued by the fertilizer factory. Treatment of single N-P-Ca fertilizer dose and compound NPCa fertilizer. The data were analyzed statically by analysis of variance and the difference in the mean value was calculated by the list significant difference (LSD) method at 1% and 5% levels. The single N-P-Ca and compound NPCa fertilizer treatments obtained good results compared to those without fertilizer application (control). Plant height growth, growth in the number of tillers, fresh material production and leaf percentage production obtained the best results in the single N-P-Ca treatment compared to the compound NPCa treatment at various levels. It can be concluded that, if using inorganic fertilizer, it is better to use single N-P-Ca fertilizer compared to compound NPCa fertilizer